Dynamics of sensory perceptions in arabica coffee brews with different roasting degrees. Issue 5 (3rd September 2019) - Barbosa, Mayara de Souza Gois; Francisco, Julyene Silva; dos Santos Scholz, Maria Brigida; Kitzberger, Cíntia Sorane Good; Benassi, Marta de Toledo
ABSTRACT: Temporal Dominance of Sensations (TDS) technique was used to assess the temporal aspects of the sensory perception of coffee brew attributes. Two arabica coffees with differences in the composition were roasted to two different roasting degrees (medium-light and dark). The medium-light roast process induced to higher differences in brews composition that were related to more diversity in TDS profiles. The bitter taste and roasted flavor were the dominant attributes in dark roasted coffee brews, while in the medium-light roasted, the sour taste was highlighted. In general, high acidity and high caffeine content favored the dominance of astringent and sour taste in the brews, while a high content of chlorogenic acids favored the dominance of the bitter taste.